AIRCRAFT LANDING FLARE - Kovalevskiy, Eduard; Konin, Valeriy; Olevinska, Tetiana (Proceedings of National Aviation University (archive), 2014)
The method of aircraft flare onto airfield surface using ground speed and altitude exponential step change is considered. A Math modeling of this method has been performed